Joint Decoding Order and Power Allocation Design for a NOMA-Based Overlay Cognitive Integrated Satellite-Terrestrial Relay Network. (1st April 2022) - Liu, Rui; Guo, Kefeng; An, Kang; Zhu, Shibing; Shuai, Haifeng
Abstract : Due to the shortage of spectrum resources, a nonorthogonal multiple access- (NOMA-) based overlay cognitive integrated satellite-terrestrial relay network is established in this paper, where cognitive radio (CR) and NOMA scheme are utilized to enhance spectral efficiency. In this system, a secondary terrestrial transmitter assists the transmission of primary signal and transmits its own signal simultaneously. To maximize the achievable rate of a secondary network on the premise of ensuring the quality of service of primary network, the decoding order and power allocation are jointly optimized. Particularly, we first derive the optimal power allocation factor for a given decoding order. After searching all different decoding orders, the globally optimal joint design of the decoding order and power allocation is obtained. To gain deep insights, the exact and asymptotic expressions for outage probability of both primary and secondary networks are derived. Numerical results demonstrate the accuracy of our derivation and indicate the impacts of key parameters on the proposed system.